As ideias de inovações educacionais da Fundação Lemann: cartel educacional e ação privatista (2011 – 2021) - Fegadolli, Priscila Cristina do Nascimento (2023)
Brazilian politics has, over the years, resorted to the private sector to perform public services in different areas that are duties of the State. In education, it presents itself as a private option, activated by the actions of private institutions in all sectors of public education, introducing themselves as representatives of the elaboration of the guidelines of the Base Nacional Comum Curricular (BNCC), of corporate actions such as “Todos pela Educação”, as influencers of Plano de Desenvolvimento da Educação (PDE), in the preparation of the Guia de Tecnologias Educacionais, in outsourcing teacher training, in the development of teaching materials and others. Among the subjects who act in this way is Jorge Paulo Lemann with his foundation and his ideas about educational innovation. His foundation is selected as the object of this research. The objective of this research is to analyze what actions this institution has dedicated itself to in relation to education, mainly using the discourse of “educational innovation” in the form of technological evolution. It seeks to carry out a critical analysis of the educational processes carried out by the foundation to understand the meanings of what it understands as “educational innovation”, since this element seems to justify a large part of its actions on public education. To this end, several documents produced by the foundation itself and its network that was established during the privatization interference in government space will be analyzed. The research understands the idea of innovation within the complexity of time and space of history, analyzing it through the intricate game of social relations that selects what should or should not be identified as “new”, in the way thought by Williams (1992). As a result, we see that the idea of innovation is naturalized in communication and information technologies and that the use of educational space is designed to combine two practices: legitimize the foundation in a way that makes the need for the products of the cartel it heads essential; make the school a disseminating machine for neoliberal ideas, hailed by the mantle of philanthropocapitalism